STUDI PEMETAAN KOMPETENSI PROFESIMEKANIK OTOMOTIF RODA 4 DI BENGKEL OTOMOTIF DI SURAKARTA TAHUN 2012 - Mardowo, Sri Wahyu (Jurnal Nosel, 2016)
Maping of mechanic automotif competension in Surakarta. The Result, we can conlude that : (1) the profile automotive mechanic in Surakarta is relevance with Indonesian National Work Competence Standards(SKKNI), the precentage of relevance reached 88.14%. (2) The research found that there was preferred mechanical competence there were; competence attitude, encouragement, hard worker, discipline, responsibility, dedication, service, honest and creativity had level as high as 100%, obedient was 96 %, carrier planning was 92 %, service orientation 100%, honesty 100%